2020
DOI: 10.3390/ijms21239132
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms Underlying Autonomous Adrenocorticotropic Hormone Secretion in Cushing’s Disease

Abstract: Cushing’s disease caused due to adrenocorticotropic hormone (ACTH)-secreting pituitary adenomas (ACTHomas) leads to hypercortisolemia, resulting in increased morbidity and mortality. Autonomous ACTH secretion is attributed to the impaired glucocorticoid negative feedback (glucocorticoid resistance) response. Interestingly, other conditions, such as ectopic ACTH syndrome (EAS) and non-neoplastic hypercortisolemia (NNH, also known as pseudo-Cushing’s syndrome) also exhibit glucocorticoid resistance. Therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 157 publications
1
21
0
Order By: Relevance
“…Indeed, Mu Y-M et al showed that the GRα mRNA levels in the adenomas in patients who showed no response to the 8-mg dexamethasone suppression test were significantly lower than those in the adenomas in patients who showed suppression [ 40 ]. Glucocorticoid receptors may not only contribute to regulation of the ACTH production but also to the control of cortocotropinoma growth via the MAPK pathway [ 41 , 42 ]. The more aggressive behavior of silent corticotropinomas and the development of pituitary macroadenoma in Nelson syndrome [ 43 ] may confirm the hypothesis of the involvement of glucocorticoids in the negative regulation of corticotropinoma growth.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Mu Y-M et al showed that the GRα mRNA levels in the adenomas in patients who showed no response to the 8-mg dexamethasone suppression test were significantly lower than those in the adenomas in patients who showed suppression [ 40 ]. Glucocorticoid receptors may not only contribute to regulation of the ACTH production but also to the control of cortocotropinoma growth via the MAPK pathway [ 41 , 42 ]. The more aggressive behavior of silent corticotropinomas and the development of pituitary macroadenoma in Nelson syndrome [ 43 ] may confirm the hypothesis of the involvement of glucocorticoids in the negative regulation of corticotropinoma growth.…”
Section: Discussionmentioning
confidence: 99%
“…A main characteristic of the pathogenesis of pituitary ACTH-secreting adenomas is an impaired ACTH suppression by GC negative feedback, potentially caused by different molecular abnormalities. It was reported that ACTH-secreting pituitary tumors show enhanced 11HSD2 gene expression but suppressed 11HSD1 gene expression, suggesting a partial or weak GC resistance [ 30 ]. Other mechanisms possibly underlying GC resistance may be due to abnormalities in the activation and function of GR.…”
Section: Pathophysiology Of Pituitary and Adrenal Mild Hypercortisolismmentioning
confidence: 99%
“…Additionally, Brg1, which belongs to the SWitch/Sucrose NonFermentable proteins (a group of proteins that regulate the way DNA is packaged) and histone deacetylase 2 have been shown to be important for the proopiomelanocortin gene expression. Loss of either Brg1 or histone deacetylase 2 can lead to GC resistance in ACTH-secreting adenomas, since Brg1 stabilizes the interaction between GR and histone deacetylase 2 to suppress proopiomelanocortin gene transcription [ 30 ]. In summary, increased expression of the 11HSD2 gene, HSP90 or Testicular receptor 4, and loss of expression of Brg1gene or CABLES1 gene are thought to contribute to the pathogenesis of ACTH-secreting pituitary tumors by reducing the GC negative feedback system.…”
Section: Pathophysiology Of Pituitary and Adrenal Mild Hypercortisolismmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism of ACTHomas is still unclear. 2 The pituitary adenoma invasion is an important factor associated with the clinical prognosis. Endothelial cell derivedsecreted factor epidermal growth factor-like domain 7 (EGFL7), plays an important role in angiogenesis.…”
Section: Introductionmentioning
confidence: 99%